Upaya Meningkatkan Kreativitas Anak melalui Bentuk-Bentuk Geometri pada Anak Usia 4-5 Tahun di KB Permata Ibu Desa Tanjung Kecamatan Koto Kampar - Yelly Marike Oktaviani; Rahmah Rahmah; Suparmi Suparmi (Asian Journal of Early Childhood and Elementary Education, 2026)
Creativity is an important aspect of early childhood development that needs to be stimulated through engaging and meaningful learning activities. However, observations at KB Permata Ibu in Tanjung Village, Koto Kampar Subdistrict, showed that the creativity of children aged 4–5 years remained relatively low due to monotonous teaching methods, limited stimulation for creative expression, and insufficient supportive learning media. This study aimed to enhance children’s creativity through play and creative activities using geometric shapes. The study employed a classroom action research method conducted in two cycles, each consisting of planning, action implementation, observation, and reflection. The research subjects comprised 15 children aged 4–5 years at KB Permata Ibu. Data were collected through observation and documentation using a creativity observation sheet covering the ability to create products from geometric shapes, produce original work, explain the finished product, and describe the work flexibly. The data were analyzed using quantitative descriptive techniques with percentage formulas. The results showed that children’s creativity improved significantly, from 42.7% in Cycle I, Meeting 1 to 60.78% at the end of Cycle I, then increased to 71.29% in Cycle II, Meeting 1, and reached 81.92% at the end of Cycle II, categorized as developing very well. These results exceeded the predetermined success indicator of ≥75%. Thus, play and creative activities using geometric shapes were proven effective in enhancing early childhood creativity. This study implies that the use of varied, creative play-based learning media can serve as an effective strategy for early childhood education teachers in fostering children’s creativity.